Level of Competency Needs Assessment Based on Permenhub No. PM 7 of 2018 Concerning the Master Plan for Skkni Development Transportation Sector - Simanjuntak, Marihot; Malau, April Gunawan (International Review of Management and Marketing, 2019)
The determination of the Key performance Indicator (KPI) can be used to measure the level of competency needs of the transportation sector based on Permenhub No. PM 7 of 2018. In determining the KPI, weighting each statement in the questionnaire is first done, then recapitulating the total value of each respondent, ranking the competency according to the respondent's answer and presenting it in the form of a frequency distribution table . This study aims to determine the level of need from the implementation of the master plan for the development of Indonesia's national work competency standards (SKKNI) in the transportation sector . The results of the study showed that the port operators that were used as respondents really needed the competence of the non-regulator sea transportation sector ports, as evidenced by the results of the average level of competency requirements in the category of Need and Very Need. Then the application of the transportation sector SKKNI based on Permenhub No. PM 7 of 2018 must be implemented so that operators at the port have competencies in the form of knowledge and skills as well as attitude / or behavior in implementing. Keywords: scout officer, training, compete JEL Classifications: L62, R41, R42 DOI: https://doi.org/10.32479/irmm.8593